2020
DOI: 10.3390/ijerph17165819
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Mental Health Promotion Initiatives—Process Evaluation of the ABCs of Mental Health in Denmark

Abstract: Treatment and prevention alone are unlikely to make a significant difference in reducing the burden of poor mental health and mental illness. Therefore, mental health promotion (MHP) initiatives are advocated. In 2014, the ABCs of mental health (ABCs) partnership was established in Denmark; in the partnership, partner organisations, e.g., municipalities and NGOs, use a research-based framework for MHP, the ABC-framework, to develop and implement MHP initiatives. This paper has two aims: (1) to outline the over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…The adaptability of the Act-Belong-Commit domains across cultures illustrates the universality of these three domains as shown in the following examples: a pilot program in a First Nations community in Western Australia showed that the message was consistent with Indigenous people’s concepts around social and emotional wellbeing and was readily modified for a local implementation [ 48 ]; the campaign was adapted in Japan for children after the 2011 tsunami [ 49 ]; and the campaign has attracted partner organisations in the UK and USA and is being implemented in Denmark, the Faroe Islands and Norway [ 23 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The adaptability of the Act-Belong-Commit domains across cultures illustrates the universality of these three domains as shown in the following examples: a pilot program in a First Nations community in Western Australia showed that the message was consistent with Indigenous people’s concepts around social and emotional wellbeing and was readily modified for a local implementation [ 48 ]; the campaign was adapted in Japan for children after the 2011 tsunami [ 49 ]; and the campaign has attracted partner organisations in the UK and USA and is being implemented in Denmark, the Faroe Islands and Norway [ 23 , 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Formative research and subsequent feedback reinforce the simplicity of the campaign messages as summed up in the campaign’s original animated television commercial: ‘Keeping mentally healthy is just as important as keeping physically healthy and it’s as simple as a-b-c, act-belong-commit’ [ 19 ]. Members of the general population consider that the campaign messages are simple to understand and simple to interpret [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research into the development and evaluation of health promotion dialogue tools and activities inspired by a salutogenic approach appear warranted. In this regard, recent development and implementation of a mental health promotion initiative in Denmark applying a salutogenic oriented conceptual framework focussing on strengthening and promoting resources and protective factors, emphasised the importance of building capacity (including providing staff training) and campaign activities to promote awareness and knowledge (Hinrichsen et al, 2020). While the study was not related to promotion of health behaviour change per se, the study holds great promise and inspiration for advancing and promoting a resource oriented practice in the context of mental health care including fostering intersectoral and interprofessional collaborations and patient-professional co-creation (Hinrichsen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%